Preliminary chemical analysis of new discovered siderite meteorites from Croatia and Bosnia and Herzegovina - Budimčić, Jelena (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Analyzes eleven iron meteorite samples using powder diffraction, etching, and emission spectroscopy. Characterization reveals ataxite structural classification with high iridium content and iron-nickel composition.